Saussurea obvallata (Sacred Species): a Contemporary Context of Biodiversity Conservation - Bhardwaj, Meenakshi; Chauhan, N. S.; Pareek, S. K .; Naithani, Rekha; Chauhan, Rajesh (Indian Forester, 2011)
Medicinal plants require necessary conservation efforts for protection and sustainable use. Tribal community Kinnaura in Kinnaur district of Himachal Pradesh has protected and conserved Saussurea obuollala, one of the endangered plant species of the Himalayas through their social and cultural traditions and have made an exemplary contribution by exhibiting as to how their traditional values could help in biodiversity conservation.